Fiction and Representation - Vecsey, Zoltán (Meinong Studies / Meinong Studien Ser., 2019)
The series presents historical and systematic studies on the philosophy of Alexius Meinong and his school, as well as on works influenced by aspects of Meinong's philosophy. Furthermore, the series is open to contributions in the analytic-phenomenological tradition, mirroring the most recent developments in these disciplines.